STUDI KEPUASAN KERJA BAGI GENERASI MILENIAL DI DKI JAKARTA, BERDASARKAN PENGARUH DARI PENGEMBANGAN KARIR DAN KOMPENSASI - Ainun Fitri Winyanti; Andi Fariana (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
Millennial generation is a generation that has competitiveness, collaborative, and innovative, responsive to technology although sometimes referred as a generation that is impatient with something, easily distracted and tend to be self-oriented, and consider work is not just a matter of salary. For this reason, it is necessary to know whether career development and compensation factors have an influence on job satisfaction because of course there are many factors that make a worker especially millennial generation feel satisfied at work The sampel used is 145 respondent and data collection by distributing online questionnaires using Google Form. The analysis technique used in this study is classic assumption test. The result of the study which used quantitative analysis method, found that career development, and compensation have a significant positive effect on job satisfaction on millennial generation in Jakarta and for that further research is needed with a wider sample and analyze other factors.